Expolysaccharides from Bifidobacterium animalis RH activates RAW 264.7 macrophages through toll-like receptor 4. Issue 1 (2nd January 2017) - Liu, Lei; Li, Hui; Xu, Ri-Hua; Li, Ping-Lan
ABSTRACT: A water-soluble expolysaccharide (EPS) was prepared from Bifidobacterium animalis RH by enzymatic hydrolysis, ethanol precipitation and Sepharose CL-6B column chromatography. Its immunomodulating activity was evaluated using murine macrophage cell line RAW 264.7. The data obtained showed that the EPS promoted proliferation and phagocytosis activity of RAW 264.7 cells. In addition, the EPS promoted RAW 264.7 cells to produce NO, IL-6, TNF-α, MCP-1 and MIP-1α in a dose-dependent manner. Further work revealed that the EPS activated RAW 264.7 cells majorly through TLR4.